2007
DOI: 10.1126/science.1146511
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Determination of the Nanoscale Chemistry and Behavior of Solid-Liquid Systems

Abstract: Many fundamental questions in crystal-growth behavior remain unanswered because of the difficulties encountered in simultaneously observing phases and determining elemental concentrations and redistributions while crystals nucleate and grow at the nanoscale. We show that these obstacles can be overcome by performing energy-dispersive x-ray spectroscopy on partially molten Al-Si-Cu-Mg alloy particles during in situ heating in a transmission electron microscope. Using this technique, we were able to (i) determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…However, many fundamental questions regarding the segregation behavior of solute atoms remain unanswered because of the difficulties that exist for in situ experiments to determine elemental concentrations and monitor the changes of local structure around solute atoms ahead of the growing solidification front that occurs during freezing at an atomic scale. Fortunately, Eswaramoorthy et al [3] have reported a potential method to detect the in situ redistribution of alloying elements at the nanoscale. Their experimental results showed that the maximum concentration of alloying Cu in an Al matrix was at the point a small distance away from the growth interface and that the concentration of Si gradually changes as the liquid phase transitions into a faceted Si crystal.…”
Section: Introductionmentioning
confidence: 99%
“…However, many fundamental questions regarding the segregation behavior of solute atoms remain unanswered because of the difficulties that exist for in situ experiments to determine elemental concentrations and monitor the changes of local structure around solute atoms ahead of the growing solidification front that occurs during freezing at an atomic scale. Fortunately, Eswaramoorthy et al [3] have reported a potential method to detect the in situ redistribution of alloying elements at the nanoscale. Their experimental results showed that the maximum concentration of alloying Cu in an Al matrix was at the point a small distance away from the growth interface and that the concentration of Si gradually changes as the liquid phase transitions into a faceted Si crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid materials often exhibit medium and/or short range order, such as nanoscale structural motifs, clustering, or local ordering at the level of the atomic coordination spheres. Describing this local order of soft matter systems and supercritical fluids in particular is crucial for understanding the origins of their material properties [9][10][11][12][13][14]. …”
mentioning
confidence: 99%
“…[12][13][14][15] Metalcatalyzed VLS growth of semiconductor nanowires proceeds by the precipitation of semiconductor material out of metal-semiconductor eutectic melt droplets, which are supersaturated by ceaseless exposure to gas-phase semiconductor reactants above the eutectic temperature. [8][9][10] More recent works have demonstrated that semiconductor nanowires can also be grown via a VSS growth mechanism below the eutectic temperature, at which the catalysts may exist in the form of solid solution or compound(s) of metal-semiconductor.…”
mentioning
confidence: 99%